Dermatological adverse events in Chinese prostate cancer patients treated with the androgen receptor inhibitor apalutamide - Wang, Qi; Ren, Zhao-Ting; Wu, Hui-Feng; Gu, Hao-Chen; Li, Xia-Wei; Tang, Zhuang-Li (Frontiers in Immunology, 2025)
BackgroundApalutamide, an androgen receptor inhibitor, has shown good efficacy in treating prostate cancer (PCa). However, dermatological adverse events (dAEs) are common and threatening, and relevant studies in China are limited.MethodsThis was a retrospective, single-center analysis. We included PCa patients who were hospitalized and received apalutamide treatment at one comprehensive hospital in eastern China from August 2020 to March 2023. These patients were categorized into two groups for comparative analysis: those with (dAEs+) and without dAEs (dAEs–) based on the presence or absence of rash or itching following apalutamide administration. Demographics, PCa clinical and treatment data were extracted from the EMRS. The clinical features of dAEs were collected through follow-up calls.ResultsOur study enrolled 90 individuals with an overall dAEs incidence of 50.0%. All dAEs occurred within one year following apalutamide use. Over half of dAEs+ patients suffered from pruritus, erythema or papules, and the dAEs were predominantly mild to moderate. Higher PSA levels were found in patients with dAEs.ConclusionsApalutamide-associated dAEs are common in the Chinese population, among which the majority are mild to moderate, with pruritus, erythema, and papules ranking as the most prevalent symptoms. Elevated PSA levels were documented in patients with dAEs.